Effects of Online Self-Regulation Activities on Physical Activity Among Pregnant and Early Postpartum Women - Kim, Hye Kyung (2015)
Physical and psychological changes that occur during pregnancy present a unique challenge for women’s physical activity. Using a theory-based prospective design, this study examines effects of pregnant women’s (1) physical activity cognitions (self-efficacy, outcome expectancy, and safety beliefs) and (2) online self-regulation activities (goal-setting and selfmonitoring) on subsequent changes in their physical activity intentions and behavior during pregnancy and immediately postpartum. We used data from three panel surveys administered to pregnant women enrolled in a web-based intervention to promote healthy pregnancy and postpartum weight, as well as log data on their use of self-regulatory features on the intervention website. Perceived self-efficacy and perceived safety of physical activity in pregnancy enhanced subsequent intentions to be physically active. Repeated goal-setting and monitoring of those goals helped to maintain positive intentions during pregnancy, but only repeated self-monitoring transferred positive intentions into actual behavior. Theoretically, this study offers a better understanding of the roles of self-regulation activities in the processes of goal-striving. We also discuss practical implications for encouraging physical activity among pregnant and early postpartum women.